A Plausible Prebiotic Origin of Glyoxylate: Nonenzymatic Transamination Reactions of Glycine with Formaldehyde - Mohammed, Fiaz S.; Chen, Ke; Mojica, Mike; Conley, Mark; Napoline, Jonathan W.; Butch, Christopher; Pollet, Pamela; Krishnamurthy, Ramanarayanan; Liotta, Charles L. (Synlett, 2017)
Glyoxylate has been postulated to be an important prebiotic building block. However, a plausible prebiotic availability of glyoxylate has not as yet been demonstrated. Herein we report the formation of glyoxylate by means of a transamination reaction between glycine and formaldehyde in water at 50 °C and 70 °C at pH 8 and 6, respectively. The reaction was followed by means of 13C NMR and high-resolution mass spectrometry employing both unlabeled and 13C-labeled reactants. Other products accompanying the transamination process include serine, sarcosine, N,N-dimethylglycine, and carbon dioxide/bicarbonate. The mechanisms for the formation of glyoxylate and accompanying products are discussed.1 Introduction2 Background3 Results and Discussion3.1 Reaction of 13C-Labeled Glycine with Formaldehyde at pH 83.2 Reaction of 13C-Labeled Glycine with Formaldehyde at pH 63.3 Serine-Promoted Decarboxylation of Glyoxylate4 Conclusions
Keywords: prebiotic; glycine; glyoxylate; serine; transamination; decarboxylation